First Year Medical Students, Personal Handheld Ultrasound Devices, and Introduction of Insonation in Medical Education - Mollie Ireson; Simrit Warring; Jose R. Medina-Inojosa; Maria T. O'malley; Wojciech Pawlina; Nirusha Lachman; Jagat Narula; Anjali Bhagra (Ubiquity Press, 2019)
Background: Ultrasound education has been provided to students in medical schools within and beyond the United States. A formal experiment with use of personal handheld ultrasound equipment by all first-year medical students has not been reported. Employing insonation (an application of ultrasound) at the personal leisure by medical school freshmen enables self-directed learning throughout the academic year. Methods: We describe a peer-led ultrasound curriculum with handheld devices. The students' perceptions were gathered through quarterly Likert-style questionnaires, and the differences in the categories were tested using Analysis of Variance. Results: The response rate was 58.5% for the first survey (n = 32), 56% (n = 30) for the second survey, and 62.3% (n = 33) for the final survey, respectively, with an average response rate of 58.9%. At the baseline survey, overall agreement was observed for enhancement on performance (62.5%) and interpretation (56.3) of ultrasounds, understanding (68.8%) and learning of anatomy (61.3%), ease (78.1%), comfort (59.4%) and benefit of incorporation of insonation in the medical school curricula (all p-values < 0.001). Neutral response (38.7%) or disagreement (38.7%) was observed when assessing the effect of the integration in medical curriculum on specialty choice (p < 0.01). These trends remained constant over follow-up with the exception that the perceived benefit for integration of insonation into the longitudinal curricula (p < 0.05) increased significantly over time. Majority of disagreement was observed regarding current access to the personal ultrasound devices (38.7%) (p < 0.001). Conclusions: The introduction of insonation through personal handheld ultrasound devices in the first-year medical school curriculum was received enthusiastically by students, with the majority of respondents finding the devices both easy to use and a valuable aid to improving their understanding of the three-dimensional anatomy.